Moar: A Swimmer Motion Swimming Style Identification Model using Deep Learning - Al-Majnoni, Atheer; Al-Sahli, Jumana; Al-Ahmady, Dana; Al-Mutairi, Amani; Alsini, Areej; Alharbi, Manal (Engineering, Technology & Applied Science Research, 2025)
Athletes in various sports, such as swimming, are increasingly using motion capture to identify and optimize their movement techniques. However, traditional motion capture systems tend to be expensive and limited. Computer vision-based methods have emerged as alternatives to identify four swimming styles: freestyle, backstroke, breaststroke, and butterfly. However, previous models did not identify flaws in swimmer movement. A significant challenge is the lack of labeled swimming video datasets that indicate these flaws. To overcome this challenge, this study collected and labeled a dataset of swimmer flaws and integrated them with the publicly available dataset SwimXYZ. Then, YOLO models were trained on the generated data. The YOLOv8s model demonstrated an impressive mean average precision (mAP@0.50) of 98% in the detection of swimming style and 95% in the simultaneous detection of swimming style and the identification of incorrect movements. This model can be used in real-time applications to help swimmers evaluate and improve the accuracy of their techniques.